Implementasi Program Keagamaan dalam Membentuk Sikap Spiritual Peserta Didik di Madrasah Aliyah Negeri 4 Jombang: Implementasi Program Keagamaan Sikap Spiritual - Nur Efendi, vera septiana; Masruroh, Laily (Al Tadib : Jurnal Ilmu Pendidikan, 2024)
This research discusses the implementation of religious programs in shaping students' spiritual attitudes. Field research and descriptive research are used in qualitative research. Interview techniques, observation techniques and documentation were used to collect data. Deputy Head of Curriculum and Caregivers, Coaches/teachers, and Students became informants in this research. The results of the research can be concluded that the religious program implemented at Madrasah Aliyah Negeri 4 Jombang is a superior program from the Indonesian Ministry of Religion which has been designed in its teaching introduction to focus on studying religious science issues and aims to produce students to become experts in the field of religion (tafaqquh fiddin) which is achieved by deepening knowledge through the study of the yellow book and is ma'had/dormitory based which aims to help form students' spiritual attitudes through internalization and actualization of religious values. The supporting factors for the implementation of religious programs are the very adequate dormitory facilities and infrastructure, the dormitory curriculum also plays an important role in the supporting factors for the implementation of religious programs and of course the main supporting factor is the teachers/counselors who teach and transmit their knowledge, and always encourage the participants. educate them so that they are enthusiastic about learning about religious program activities.